The Economics of Tracking and Non-Tracking - Volker Meier; Gabriela Schütz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
There exists substantial variation across countries as to whether and how students are grouped in classes according to ability. Economic analyses stress that there is joint production of human capital in schools, where output increases with mean ability in the class. Ability tracking may therefore be particularly helpful for talented students. At the same time, weak students may benefit via tailored and specialised courses. The vast majority of the econometric literature suggests that tracking promotes inequality in academic achievement. By contrast, the empirical literature on the impact of tracking on average student performance is inconclusive. Only few studies find a significant association, including both positive and negative estimates.
Keywords: I20; 330; Tracking; ability grouping; peer group effects; school systems